2002
DOI: 10.1021/ja017475q
|View full text |Cite
|
Sign up to set email alerts
|

Negative Differential Resistance in Phenylene Ethynylene Oligomers

Abstract: The origin of the sharp peak profile (i.e., negative differential resistance, NDR) observed in the I/V curves of three-ring phenylene ethynylene oligomers is a topic of major current interest. Here, quantum-chemical calculations are performed to analyze the evolution of the one-electron structure of an unsubstituted three-ring oligomer under the influence of a static electric field (which models the driving voltage applied in the experiments). The results indicate that the rotation of the central ring of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 15 publications
4
79
1
Order By: Relevance
“…[25] Recently, we have demonstrated from the results of semiempirical calculations performed on the three-ring phenylene ethynylene oligomer that the rotation of the central ring by 90 can lead to an NDR signature, as a result of resonant tunneling processes occurring through the twisted ring for a very limited range of applied electric field. [26] In this contribution, we illustrate that the same mechanism applies for three-ring phenylene oligomers substituted by electroactive substituents on the central ring, for which an NDR behavior has been observed experimentally; [12,13] we also show that the resonant tunneling processes are activated as soon as the central ring is significantly twisted with respect to the plane defined by the other two rings. This picture contrasts with the initial idea that the NDR peak observed for molecule 1b is associated to an abrupt conformational change (most probably a rotation of the central substituted ring induced by the interaction between the permanent dipole moment of the molecule and the electric field).…”
Section: Introductionsupporting
confidence: 61%
“…[25] Recently, we have demonstrated from the results of semiempirical calculations performed on the three-ring phenylene ethynylene oligomer that the rotation of the central ring by 90 can lead to an NDR signature, as a result of resonant tunneling processes occurring through the twisted ring for a very limited range of applied electric field. [26] In this contribution, we illustrate that the same mechanism applies for three-ring phenylene oligomers substituted by electroactive substituents on the central ring, for which an NDR behavior has been observed experimentally; [12,13] we also show that the resonant tunneling processes are activated as soon as the central ring is significantly twisted with respect to the plane defined by the other two rings. This picture contrasts with the initial idea that the NDR peak observed for molecule 1b is associated to an abrupt conformational change (most probably a rotation of the central substituted ring induced by the interaction between the permanent dipole moment of the molecule and the electric field).…”
Section: Introductionsupporting
confidence: 61%
“…Some groups experimentally and theoretically observed NDR in many physical systems such as oligo (phenylene ethynylene) (OPE) molecular devices with semiconductor electrodes [20], doped and squashed C 60 molecular device [21], porphyry molecular junctions modulated with side groups, CNTs or heterojunctions with the metal electrodes [22]. Possible mechanisms have been proposed to explain the NDR behavior, such as the variation of the coupling between the molecular orbital and the incident states from the electrodes at different bias voltages [20], the channel conduction being suppressed at a certain bias [22], the resonant and off resonant electronic tunneling mechanism [25], the biasinduced alignment of molecular orbitals [26], side group effects [27], and the splitting of the molecular orbitals [28]. In spite of a number of studies about NDR in various kinds of molecular devices, the origin for NDR is still under intense debate due to their structural complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Based on such studies, Seminario et al proposed that charging of the molecule and subsequent localization/delocalization of molecular orbitals is the microscopic mechanism behind NDR, 8,9 while Cornil et al have found that bias-induced alignment of molecular orbitals on the first and last phenyl rings of twisted TW's can lead to NDR. 10 In this paper we present the first studies of the electrical properties of functionalized TW's covalently bound to gold surfaces. Most prominent previous studies of related systems include the IV characteristics of a functionalized benzene ring 13 and a bare TW.…”
mentioning
confidence: 99%